Re-thinking global health sector efforts for HIV and tuberculosis epidemic control: promoting integration of programme activities within a strengthened health system - Maher Dermot (BMC, 2010)
Abstract Background The global financial crisis threatens global health, particularly exacerbating diseases of inequality, e.g. HIV/AIDS, and diseases of poverty, e.g. tuberculosis. The aim of this paper is to reconsider established practices and policies for HIV and tuberculosis epidemic control, aiming at delivering better results and value for money. This may be achieved by promoting greater integration of HIV and tuberculosis control programme activities within a strengthened health system. Discussion HIV and tuberculosis share many similarities in terms of their disease burden and the recommended stratagems for their control. HIV and tuberculosis programmes implement similar sorts of control activities, e.g. case finding and treatment, which depend for success on generic health system issues, including vital registration, drug procurement and supply, laboratory network, human resources, and financing. However, the current health system approach to HIV and tuberculosis control often involves separate specialised services. Despite some recent progress, collaboration between the programmes remains inadequate, progress in obtaining synergies has been slow, and results remain far below those needed to achieve universal access to key interventions. A fundamental re-think of the current strategic approach involves promoting integrated delivery of HIV and tuberculosis programme activities as part of strengthened general health services: epidemiological surveillance, programme monitoring and evaluation, community awareness of health-seeking behavior, risk behaviour modification, infection control, treatment scale-up (first-line treatment regimens), drug-resistance surveillance, containing and countering drug-resistance (second-line treatment regimens), research and development, global advocacy and global partnership. Health agencies should review policies and progress in HIV and tuberculosis epidemic control, learn mutual lessons for policy development and scaling up interventions, and identify ways of joint planning and joint funding of integrated delivery as part of strengthened health systems. Summary As both a danger and an opportunity, the global financial crisis may entail disaster or recovery for global health sector efforts for HIV and tuberculosis epidemic control. Review of policies and progress in control paves the way for identification of synergies between the two programmes, within strengthened health services. The silver lining in the global economic crisis could be better control of the HIV and tuberculosis epidemics, better overall health system performance and outcomes, and better value for money.